2019
DOI: 10.1371/journal.pone.0213195
|View full text |Cite
|
Sign up to set email alerts
|

A multidisciplinary study of pain in cats undergoing dental extractions: A prospective, blinded, clinical trial

Abstract: This study aimed to evaluate pain scores, analgesic requirements, food intake and serum inflammatory cytokines in cats before and after clinically recommended dental treatment. Twenty-four cats were included in a prospective, blinded clinical trial. Cats were equally divided into minimal (minimal dental treatment) or severe (multiple dental extractions) oral disease groups. They were admitted (day 0) and underwent oral examination/radiographs/treatment under general anesthesia (day 1; acepromazine-hydromorphon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 28 publications
(23 reference statements)
1
36
0
2
Order By: Relevance
“…Descriptive statistics for age, body weight, body condition score, dental score and number of extracted teeth are presented in Table 1. Cats in the minimal oral disease group were younger and lighter than those in the severe oral disease group as previously reported [12] (Table 1).…”
Section: Resultssupporting
confidence: 77%
See 4 more Smart Citations
“…Descriptive statistics for age, body weight, body condition score, dental score and number of extracted teeth are presented in Table 1. Cats in the minimal oral disease group were younger and lighter than those in the severe oral disease group as previously reported [12] (Table 1).…”
Section: Resultssupporting
confidence: 77%
“…This study identified specific pain-induced behaviors associated with oral disease in cats undergoing dental treatment. According to our hypotheses, these behaviors differed between cats with minimal and severe oral disease, and new behaviors appeared after the dental procedure due to postoperative pain [12]. Overall, cats with severe oral disease were less active when compared with baseline or cats with minimal oral disease.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations